The Implementation Of STEM-Based Learning to Enhance Students’ Creative Thinking Skills - Salma Fauziyyah; Dwi Sulisworo (Jurnal Penelitian Pembelajaran Fisika, 2026)
Creative thinking skills are a crucial competency required in 21st century education, where innovation and problem solving abilities are increasingly emphasized. STEM based learning (Science, Technology, Engineering, and Mathematics) is considered a potential approach to develop these cognitive capacities; however, a comprehensive synthesis of empirical evidence is needed to validate its effectiveness in secondary school contexts. Therefore, this study aims to analyze the implementation of STEM based learning in enhancing students’ creative thinking skills. This study employs a systematic review approach by analyzing and synthesizing data from various quasi experimental studies that examine STEM learning interventions. The findings indicate that STEM based learning consistently leads to significant improvements in creative thinking skills, particularly in fluency and originality. Project based, inquiry based, and Ethno STEM models are identified as the most effective approaches compared to conventional learning. However, improvements in flexibility and elaboration tend to be more limited, influenced by factors such as implementation duration, teacher readiness, and insufficient scaffolding. Overall, the findings confirm that STEM based learning is an effective approach for fostering students’ creative thinking skills and provides practical implications for educators in designing more optimal instructional strategies to support comprehensive creativity development.